New chopper modulators using differential voltage current conveyor - Kumngern, Montree (Společnost pro radioelektronické inženýrství, 2011)
This paper presents new chopper modulators which can enable to assign three modulators in one circuit. Full amplitude modulators as Cowan and Ring modulators are kinds of the amplitude modulators as well. The proposed circuit is implemented from the differential voltage current conveyor, four-MOS transistors switch and two-MOS transistors inverter. The advantage of this proposed circuit is high input and low output impedance and is able to be connected with any load without buffer and the number of transistors is quite less which is suitable for integrated circuits. The technique is to control the switch by using the square pulse which is obtained from a direct signal generator. All simulation results are based on the PSPICE program simulator which confirms the performance of the proposed circuit and technique.
Keywords: chopper modulator; differential voltage current conveyor; Cowan modulator; ring modulator; AM modulator